2020
DOI: 10.1039/d0qi00577k
|View full text |Cite
|
Sign up to set email alerts
|

Combined DFT and geometrical–topological analysis of Li-ion conductivity in complex hydrides

Abstract: On the basis of DFT calculations, the Li-ion migration was analyzed for LiBH4, LiNH2, Li2NH, Li2BH4NH2, Li4BH4(NH2)3 and Li5(BH4)3NH complex hydrides by means of the nudged elastic band method. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 49 publications
(64 reference statements)
5
15
0
Order By: Relevance
“…The so-obtained E a is equal to 0.29 ± 0.03 eV below 60 °C. The obtained E a is considerably lower than the average value reported in the literature for pure LiBH 4 (0.75 ± 0.07 eV), 41 but it is similar to values observed for other SSEs. 42 …”
Section: Results and Discussionsupporting
confidence: 83%
“…The so-obtained E a is equal to 0.29 ± 0.03 eV below 60 °C. The obtained E a is considerably lower than the average value reported in the literature for pure LiBH 4 (0.75 ± 0.07 eV), 41 but it is similar to values observed for other SSEs. 42 …”
Section: Results and Discussionsupporting
confidence: 83%
“…The background was described through a polynomial function with 3 or 4 parameters. The following sequence was applied for the refinement of parameters: (1) scale factor (2) background parameters (3) lattice constants (4) crystallites size (5) micro-strain. In some cases, also the occupancy and the position of the 2b site in the hexagonal structure were refined.…”
Section: Rietveld Analysismentioning
confidence: 99%
“…3 In 2007, Matsuo et al 4 reported a drastic increase of the Li-ion conductivity of LiBH4 above the phase transition temperature, suggesting it as a solid-state electrolyte. Despite the hexagonal polymorph (h-LiBH4) shows a remarkable ionic conductivity (~10 −3 S cm -1 at 120 °C), the orthorhombic room temperature phase (o-LiBH4) is much less conductive, showing a Li-ion conductivity of 9.5 × 10 −9 ± 2 × 10 −9 S cm -1 at 30 °C, 5 making a room temperature battery target unviable. 4 Different approaches have been used to increase the Li-ion conductivity of LiBH4 at RT, such as by mixing it with oxides or by means of nanoconfinement.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have used few representative structures with distinct migration topologies to derive rules for the migration in multivalent magnesium battery materials [7,10] . Geometrical investigations in combination with cheaper computational methods based on Bond Valence Site Energies (BVSE) [11] or DFT calculations on a few selected structures [12] have been conducted. They discussed the importance of being able to describe the geometry of the transition state along the migration path in order to predict kinetic barriers.…”
Section: Introductionmentioning
confidence: 99%